Correction: Method for extraction and analysis of per- and poly-fluoroalkyl substances in contaminated asphalt. Issue 35 (25th August 2022) - Srivastava, Prashant; Williams, Mike; Du, Jun; Navarro, Divina; Kookana, Rai; Douglas, Grant; Bastow, Trevor; Davis, Greg; Kirby, Jason K.
Abstract : Correction for 'Method for extraction and analysis of per- and poly-fluoroalkyl substances in contaminated asphalt' by Prashant Srivastava et al., Anal. Methods, 2022, 14, 1678–1689, ; https://doi.org/10.1039/D2AY00221C .